2022
DOI: 10.1371/journal.pstr.0000009
|View full text |Cite
|
Sign up to set email alerts
|

Food security and small holder farming in Pacific Island countries and territories: A scoping review

Abstract: UN Sustainable Development Goal (SDG) 2: Zero Hunger links ending hunger to achieving food security, improving nutrition, and promoting sustainable agriculture. The Pacific Island Countries and Territories (PICTs) is a region where such linkages can be investigated as the PICTs are confronting climate change while facing a decrease in available arable land and increasing rates of urbanisation. Around 80% of all Pacific Islanders still rely on agricultural produce from their own gardens or from small holder far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 42 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…Subsistence farming and handicrafts are also major sources of income. The majority of households, particularly on the outer islands, are self-sufficient (Georgeou et al 2022). Source: The World Bank, data bank.…”
Section: Fiji Kiribati Samoa and Tonga: Economic Situation And Labor ...mentioning
confidence: 99%
“…Subsistence farming and handicrafts are also major sources of income. The majority of households, particularly on the outer islands, are self-sufficient (Georgeou et al 2022). Source: The World Bank, data bank.…”
Section: Fiji Kiribati Samoa and Tonga: Economic Situation And Labor ...mentioning
confidence: 99%
“…The results showed that integrated farming had contributed to the fulfillment of food needs; almost all of the commodities planted have highly contributed to the food needs of the people of Payung Island. In Pacific Island, the farmers planted different crops both for food and for sale and They had growed local foods to support food security and expanding domestic asset creation to promote economic development [6]. In Payung island, kangkong gave the largest contribution to vegetable crops which reach to 564.90%.…”
Section: The Contribution Of Integrated Agriculture To the Fulfillmen...mentioning
confidence: 99%
“…Agricultural practices in small islands will have an impact on food security, economic welfare and environmental sustainability [4] and it has the added benefit of promoting economic development for women and employment for young people [5]. In Solomon island, the role of women in the archipelago is very important in helping the family economic [6]. However, marginal land has various limitations for agricultural use, including sandy land conditions, low soil fertility, limited availability of fresh water, and minimal availability of fertilizers, less of agricultural human resources.…”
Section: Introductionmentioning
confidence: 99%
“…Torres Strait Islanders in the South Pacific, for example, have historically dealt with non-anthropogenic climate change, and have culturally evolved practices for tracking seasonal weather patterns and timing crop planting that have not widely diffused to all who might benefit from adopting them [14]. Adaptive practices like this for subsistence farming will soon be widely in demand due to anthropogenic climate change [27]. Such practices tend to diffuse predominantly through person-to-person or household-to-household learning [28,29].…”
Section: Introductionmentioning
confidence: 99%